Truth is Concrete : A Handbook for Artistic Strategies in Real Politics - Malzacher, Florian; Boyd, Andrew; Bruguera, Tania; Cuevas, Minerva; Cummings, Neal; Esche, Charles; Fraser, Andrea; Geller, Frederico; Harney, Stefano; Jonas, Staal; Lovink, Geert; Lucchetti, Matteo; et al. (Berlin : Sternberg Press, 2015)
The Silent University ; Haacke, Hans ; Chto delat ; Neue Slowenische Kunst ; Tancons, Claire ; Mroué, Rabih ; Arte Util ; Hourani, Khaled ; Liberate tate ; The Institute for Human Activities ; Tahrir cinema ; Artleaking ; Observatorio de Favelas ; Occuprint ; The Yes Men ; Public Movement ; Office for Anti-Propaganda ; Occupy.
catalogus naar aanleiding van het jaarlijkse festival Steirischer Herbst, Graz, 2012
boek